Implementation of Green Technologies in Building Maintenance, Repair and Rehabilitation for The Historical Building - Mohd Khairi, Harith Syahmi; Abdul Rahman, Mohammad Ashraf (Progress in Engineering Application and Technology, 2022)
In order to realise the potential of environmentally conscious upkeep practises, historic buildings need to be equipped with the appropriate infrastructure. A preliminary investigation into the historic building maintenance plan found that the use of green technology in heritage building maintenance is still at a modest level and needs further development. A lack of knowledge of the need of maintaining historic buildings with components of environmentally friendly technology has been identified as a significant factor that contributes to the prevalence of such practises. The historical building will benefit from the use of environmentally friendly building care, repair, and rehabilitation practises, which are the aim of this research. The fundamental objective of this study is to identify the role that environmentally friendly technologies play in the operation of building maintenance, repair, and rehabilitation processes for the historical building. These methods consider a variety of elements, including the aspect of green technology that provides the best upkeep for historic structures. In order to gather information for the study, questionnaires were sent to historic building experts. For the purpose of the inquiry, the History and Ethnography Museum, The People's Museum, and The Governor's Museum are the three buildings that have been selected to compete with one another to determine which the best heritage building museum.